Primer Congreso Jurídico Nacional - Olarte Camacho, Vicente; Mendoza, Diego; Gómez Cuéllar, Ramón; Fajardo, Manuel M.; Posada, Eduardo; Quijano, Arturo (Estudios de Derecho, 1919)
Primer Congreso Jurídico Nacional